Introduction to 3G mobile communications - Korhonen, Juha (Artech House mobile communications series., 2003)
This newly revised edition of an Artech House bestseller provides you with an up-to-date introduction to third generation (3G) mobile communication system principles, concepts, and applications. The book clearly presents the basics of UMTS systems in one comprehensive volume, without bogging you down with advanced mathematics. The second edition includes an even more thorough treatment of potential 3G applications and descriptions of new, emerging technologies such as 3G System Release number 5, HSDPA, and Multimedia Broadcast/Multicast Service (MBMS). It also features discussions on both 3GPP and 3GPP2 evolution paths, the specification process, and future 3G upgrades. You get a complete overview of UMTS systems, information on the latest 3G technology standards, a review of the wideband CDMA air interface, network architecture details, and guidance in network planning and management. Other key topics include new concepts in the UMTS network, 3G system signaling procedures, 3G services and applications, modulation and coding, and standardization organizations and industry groups. An exhaustive list of references, including key website addresses, is provided in every chapter to help you gain access to further information.